Odpowiedzi

Najlepsza Odpowiedź!
2010-02-21T16:55:38+01:00
1) an=a₁+(n-1)r
a) a₁=4, r=-4, n=14
an=4+(14-1)* (-4)
an=4+13* (-4)
an=4-52
an=-48

b)a₁=1, r=0,5, n=20
an=1+(20-1)* 0,5
an=1+9,5
an=10,5

2)
a)a1=6, a3=20

a₁=6
a₃=20

a₁=6
a₁+2r=20

a₁=6
6+2r=20

a₁=6
2r=14

a₁=6
r=7

wzór ogólny: an=a₁+(n-1)r do którego podstawiamy teraz liczby
an=6+(n-1)*7
an=6+7n-7
an=7n-1 <------- wzór !


b)a1=-4, a4=5

a₁=-4
a₄=5

a₁=-4
a₁+3r=5

a₁=-4
-4+3r=5

a₁=-4
3r=9

a₁=-4
r=3

wzór ogólny: an=a₁+(n-1)r do którego podstawiamy teraz liczby
an=-4+(n-1)*3
an=-4+3n-3
an=3n-7 <------- wzór !